Herold's internal medicine : lecture oriented systematic and accurate representation of the complete topic catalogue for the medical examination for physicians - Herold, Gerd (Gerd Herold, 2010)
Textbook is a lecture oriented representation taking account of the topic catalogue for the medical examination for physicians. It is one of the leading textbooks of internal medicine in Germany, if not the leading one. Its enormous popularity is based on the facts that it represents the topics of internal medicine in an accurate and systematic form and that it has been updated every year since 1982. From content: Gastroenterology, Salt and water homeostasis, Nephrology, Rheumatology, Metabolic system disorders, Endocrinology, Angiology, Infectious diseases.